Finnish pre-service language teachers’ understanding of culture – from cultural humility to social justice - Heikkola, Leena Maria; Maijala, Minna; Merijärvi, Soila; Laine, Päivi; Mutta, Maarit (Walter de Gruyter GmbH, 2026)
Immigration to Finland has increased significantly over the past decade. As Finnish schools become more diverse, teachers must develop their cultural competence – their ability to work respectfully with people from different cultures. An even deeper understanding of supporting social justice in education can be achieved through cultural humility, which is the ability to recognize one’s own cultural biases and be open to seeing things from another culture’s point of view. Until now, this concept has not been investigated in education. Thus, the aim of this study was to investigate pre-service language teachers’ (n = 26) understandings of culture, cultural humility and social justice. The data consisted of responses to three open-ended questions in an online survey. The data were analysed qualitatively using theory- and data-driven content analysis. The pre-service teachers understood culture primarily in terms of customs and traditions but had a relatively sound understanding of social justice; however, it was mainly based on human rights, with only a few mentions of human obligations. They had only a developing understanding of cultural humility. Based on our results, pre-service language teachers may become better equipped to advocate for social justice in education if cultural humility is included in teacher training.